Evaluation of Digital Project Based Blended Learning Model to Improve Students’ Critical Thinking and Problem Solving Skills - Kurniawan, Dydik; Masitoh, Siti; Bachri, Bachtiar Sjaiful; wahyuningsih, Tri; Mulawarman, Widyatmike gede; Vebibina, Almaida (Journal of Ecohumanism, 2024)
In the digital era, there is a growing demand for innovative educational models that foster critical thinking and problem-solving skills. This study evaluates the effectiveness of the Digital Project-Based Blended Learning (DPBBL) model in enhancing these competencies among university students in Kalimantan, Indonesia. Utilizing a mixed-methods approach, the research combined quantitative analysis through a pre-test and post-test design with qualitative insights from interviews and focus group discussions. The study involved 548 students from multiple universities, with data analyzed using paired t-tests, N-Gain scores, and thematic analysis. The findings revealed a statistically significant improvement in students’ critical thinking (pre-test mean = 47.01; post-test mean = 82.67) and problem-solving skills (pre-test mean = 50.52; post-test mean = 79.87) after implementing the DPBBL model. The N-Gain scores indicated moderate effectiveness, with 66.79% for critical thinking and 58.63% for problem-solving. Qualitative feedback further highlighted increased student engagement, motivation, and collaborative learning. However, challenges in defining and proposing solutions were identified, suggesting the need for more structured support during the project phases. The study concludes that the DPBBL model is a promising pedagogical approach for integrating digital tools to develop essential cognitive skills in higher education. The results underscore the importance of combining project-based learning with blended instructional strategies to address the demands of the 21st-century workforce. Future research should explore scaling this model across diverse educational contexts to validate its broader applicability.